1999
DOI: 10.1148/radiology.211.3.r99jn45629
|View full text |Cite
|
Sign up to set email alerts
|

Liver Tumors: Utility of Characterization at Dual-Frequency US

Abstract: Changes in CNRs of relatively high- and low-frequency US images may give useful information on the frequency dependence of backscattering, which is descriptive of the histologic findings in lesions and which is not evident with conventional US images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The relatively large variance here is partially because of the small size of the scatterers in the test phantom and, therefore, a suboptimal ka range). For larger scatterer sizes, like normal liver tissue [41], the variance is expected to be smaller. However, for highly cellular malignant tumors, which appear to have smaller scatterer sizes [11, 41], the large variance may be a challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively large variance here is partially because of the small size of the scatterers in the test phantom and, therefore, a suboptimal ka range). For larger scatterer sizes, like normal liver tissue [41], the variance is expected to be smaller. However, for highly cellular malignant tumors, which appear to have smaller scatterer sizes [11, 41], the large variance may be a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…For larger scatterer sizes, like normal liver tissue [41], the variance is expected to be smaller. However, for highly cellular malignant tumors, which appear to have smaller scatterer sizes [11, 41], the large variance may be a challenge. For the depths considered (1 – 5cm for the VFX13-5 and 2 – 9cm for the VFX9-4), the shallower the objects are, the larger the useful bandwidth is and the smaller is the correlation between A-lines.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of faster and more robust technology implemented in the hardware and software of modern machines, the knowledge of certain characteristics of a scanner-transducer pair is more critical. For instance, the frequency dependence of scattering has been shown to be a useful diagnostic tool in certain diseases, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] but the information related to the actual operating frequency of a scanner is usually inadequately presented to the clinician to enable assessment of any relationship between echo signal levels and ultrasonic frequency. 15,16 The increased use of harmonic imaging in static and dynamic procedures is on the rise, and the use of this modality could benefit from knowledge of the frequency content of the scanner at various positions in the ultrasonic field.…”
mentioning
confidence: 99%
“…Therefore, scatterer size information may be very useful to differentiate them. Sommer et al [6] showed B-mode image changes with frequency that are consistent with this idea.…”
Section: In Vivo Human Liver Hemangioma Imagesmentioning
confidence: 62%